A review of the western Pacific species of the crangonid genus Metacrangon Zarenkov, 1965 (Decapoda: Caridea), with descriptions of seven new species - Komai, Tomoyuki (Zootaxa, 2012)
A review of species of the crangonid genus Metacrangon Zarenkov, 1965 (Decapoda: Caridea) from the Northwest andtropical Southwest Pacific Ocean is presented. Twenty-one species, including seven new to science, are recognized: M.asiaticus (Kobjakova, 1955) from the Kuril Islands and Komandor Islands; M. bythos n. sp. from Japan; M. clevai n. sp.from the Solomon Islands and Vanuatu; M. cornuta Komai & Komatsu, 2009 from Japan; M. holthuisi Komai, 2010 fromJapan; M. karubar n. sp. from Indonesia to Solomon Islands; M. laevis (Yokoya, 1933) from northern Japan and the Rus-sian Far East; M. longirostris (Yokoya, 1933) from Japan; M. miyakei Kim, 2005 from Japan; M. monodon (Birshtein &Vinogradov, 1951) from the North Kuril Islands; M. nipponensis (Yokoya, 1933) from Japan; M. obliqua n. sp. from Ja-pan; M. ochotensis (Kobjakova, 1955) from the South Kuril Islands; M. proxima Kim, 2005 from Japan; M. punctata n.sp. from Indonesia, Solomon Islands and New Caledonia; M. robusta (Kobjakova, 1935) from the Sea of Japan and theSea of Okhotsk; M. similis Komai, 1997 from Japan; M. sinensis Fujino & Miyake, 1970 from the northern part of the EastChina Sea; M. trigonorostris (Yokoya, 1933) from Japan; M. tropis n. sp. from Japan; and M. tsugaruensis n. sp. fromJapan. These species are classified into two informal species groups. The new species are fully described and illustrated.Some previously known species, for which detailed descriptions along modern standards are deemed necessary, are rede-scribed. Metacrangon asiaticus is elevated from a subspecies of M. variabilis to full species status. A key to aid in theidentification of the western Pacific species is provided. Bathymetrical and geographical distributions of the treated spe-cies are summarized. It is strongly suggested that each species is highly localized. The species richness is highest in waters around the Japanese Archipelago (17 of the 41 known species occur in the areas).